A method for preparing a bifunctional heterogeneous catalyst and its application in catalyzing the cycloaddition conversion of CO2 and epoxides

By loading the ionic liquid onto the metal organic frame, a dual-function heterophase catalyst was prepared, which solved the high cost and difficulty in recycling of ionic liquids in industrial production, and achieved efficient catalytic effect of cycloaddition reaction between CO2 and epoxide.

CN116586113BActive Publication Date: 2025-04-11ZHEJIANG SCI-TECH UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310596968.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-25
Publication Date
2025-04-11
Estimated Expiration
2043-05-25

AI Technical Summary

Technical Problem

In the prior art, ionic liquids are difficult to use as catalysts in industrial production, mainly because their high cost and the formed homogeneous catalytic system are not conducive to recycling and recycling treatment.

Method used

By combining the ionic liquid with a metal organic frame (MOF), a supported heterogeneous catalyst is prepared, the specific method includes loading the ionic liquid F-IL-CP onto ZIF-8 to form a 1% F-IL-CP@ZIF-8 catalyst.

Benefits of technology

The effective assembly of ionic liquid and MOF is achieved, forming a bifunctional heterogeneous catalyst with excellent performance, with a large specific surface area, good recovery performance and stability, and is suitable for cycloaddition reactions of CO2 and epoxides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116586113B_ABST
    Figure CN116586113B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a bifunctional heterogeneous catalyst, wherein an IL@MOF composite material is prepared by loading an ionic liquid onto ZIF‑8 by a solid phase synthesis method, and is applied to the cycloaddition reaction of CO2 and epoxide. By comparing the catalytic performance of ionic liquids with different loading amounts, it is found that the activity effect is optimal when the loading amount is 1.0%, and an excellent conversion rate of cyclic carbonate is shown under solvent-free and co-catalyst conditions. The composite material synthesized at the same time has a large specific surface area, good recyclability and good stability, and is a composite catalyst of ionic liquid and MOF with excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of industrial catalysts and relates to a method for preparing a catalyst for the cycloaddition reaction of CO2 and epoxides, and specifically to a method for preparing a bifunctional multiphase catalyst. The prepared multiphase catalyst can be used in catalyzing the cycloaddition conversion of CO2 and epoxides. Background Art

[0002] Metal organic frameworks (MOFs) are a unique porous crystalline material assembled by coordination bonds between metal ions and organic ligands. They are representative crystalline porous materials with high specific surface area, adjustable pore structure, and diverse composition. They have attracted much attention as a design for efficient heterogeneous catalysts. At the same time, MOFs have been proven to have broad application prospects in CO2 separation and CO2 capture. Metal nodes provide acid or base sites and combine high porosity to make it easier to attract gas molecules such as CO2, which is conducive to the addition of CO2 to form cyclic carbonates. Therefore, MOF materials are widely used as catalysts for CO2 cycloaddition conversion. For example: Cao et al. synthesized a pyrazole zinc MOF composed of Ni (salen) bipyrazole ligands and Zn clusters. The pyrazole zinc connection enables the MOF to withstand acid and base treatment and boiling water. The synthesized MOF is applied to epoxide cycloaddition reactions and exhibits high catalytic activity and excellent recyclability. The catalytic activity of styrene oxide was studied with the model substrate under the reaction conditions of 80°C and 7 MpaCO2 pressure when tetrabutylammonium bromide (TBAB) was added, and the conversion rate of cyclic carbonates could reach 99%. Rani et al. synthesized a series of metal organic frameworks based on trimesic acid by a solvent thermal method, and studied the catalytic performance in the cycloaddition reaction of CO2 and epoxides by introducing different transition metals (Co, Ni, Cu, Zn). The conversion rate of zinc-based MOF cyclic carbonates reached 94% at 120°C and 0.7 MpaCO2 pressure.

[0003] Ionic liquids are organic salts that are liquid at room temperature and are composed of organic cations and inorganic or organic anions. As a new type of polar solvent, ionic liquids have almost no vapor pressure, are non-flammable, non-volatile, have good chemical and thermal stability, are recyclable, and are environmentally friendly. They have excellent performance in the absorption and conversion of CO2. However, most ionic liquids are difficult to use in industrial production due to their high cost, and the homogeneous catalytic system they form is not conducive to their recycling and recycling. In order to solve this problem, combining ionic liquids with metal organic frameworks to form a supported heterogeneous catalytic system is also a hot research direction. Summary of the invention

[0004] The purpose of the present invention is to disclose a method for preparing a bifunctional heterogeneous catalyst to achieve the assembly of ionic liquid and metal organic framework.

[0005] Another object of the present invention is to disclose the use of the above-mentioned bifunctional heterogeneous catalyst in catalyzing the cycloaddition conversion of CO2 and epoxide.

[0006] 1. Preparation of bifunctional heterogeneous catalysts

[0007] A method for preparing a bifunctional heterogeneous catalyst comprises the following steps:

[0008] 1) Synthesis of tetrafluoro-1,4-di(bromomethyl)benzene

[0009] With dichloromethane as solvent and triphenylphosphine as initiator, tetrafluoro-1,4-di(hydroxymethyl)benzene and carbon tetrabromide are stirred and reacted at room temperature for 20-24 hours, washed, filtered and vacuum dried to obtain tetrafluoro-1,4-di(bromomethyl)benzene; the molar ratio of tetrafluoro-1,4-di(hydroxymethyl)benzene to carbon tetrabromide is 1:(2-5), and the molar ratio of triphenylphosphine to carbon tetrabromide is 0.8:1-1:1.2.

[0010] 2) Synthesis of F-IL-CP ionic liquid

[0011] Tetrafluoro-1,4-di(bromomethyl)benzene and tricyclohexylphosphine are co-dissolved in dichloromethane, stirred and reacted at room temperature for 20-24 hours, washed and filtered, and vacuum dried to obtain F-IL-CP ionic liquid; the molar ratio of tetrafluoro-1,4-di(bromomethyl)benzene to tricyclohexylphosphine is 1:1.5-1:2.5.

[0012] Synthesis mechanism of F-IL-CP ionic liquid:

[0013]

[0014] 3) Synthesis of catalyst 1%F-IL-CP@ZIF-8

[0015] Zinc oxide, 2-methylimidazole and F-IL-CP ionic liquid were ground and mixed, reacted at 160°C for 24 hours, washed and dried to obtain the catalyst 1% F-IL-CP@ZIF-8. The molar ratio of zinc oxide to F-IL-CP ionic liquid was 40-60:1, and the molar ratio of zinc oxide to 2-methylimidazole was 1:1.5-1:2.5.

[0016] 2-Methylimidazole is used as an organic ligand, and there are more N atoms on the imidazole ring that can bind to metals.

[0017] 2. Characterization of Bifunctional Heterogeneous Catalysts

[0018] The synthesized 1%F-IL-CP@ZIF-8 catalyst was characterized by X-ray powder diffraction (XRD), thermogravimetric analysis (TGA), nitrogen adsorption and desorption, CO2 adsorption, scanning electron microscopy (SEM), and transmission electron microscopy (TEM).

[0019] 1. SEM and TEM characterization

[0020] In order to understand the morphological differences between ZIF-8 loaded with ionic liquid and ZIF-8 without ionic liquid, we performed transmission electron microscopy and scanning electron microscopy on ZIF-8 and 1% F-IL-CP@ZIF-8. The results are as follows: Figure 1 As shown. Figure 1 Comparing (b~d) with (a), it can be seen that the morphology of ZIF-8 loaded with ionic liquid is similar to that of ZIF-8 not loaded with ionic liquid, both of which are regular hexahedrons, indicating that the loading of ionic liquid has not caused much change in the morphology of ZIF-8. Some structural changes may be due to uneven grinding resulting in incomplete structure.

[0021] 2. X-ray powder diffraction pattern analysis

[0022] In order to detect the crystallinity of the samples, we performed X-ray powder diffraction analysis on the synthesized samples. The results are as follows Figure 2 As shown. Figure 2 It can be seen that the peaks of the synthesized ionic liquid catalysts with different loading amounts are in good agreement with the peaks of ZIF-8 calculated by simulation, indicating that the purity of the synthesized catalyst phase is good.

[0023] 3. Thermogravimetric analysis

[0024] TGA analysis of 1% F-IL-CP@ZIF-8 catalyst was performed under N2 atmosphere to investigate the thermal stability of the catalyst. Figure 3 As shown, it was found that the initial thermal decomposition temperature of the synthesized 1% F-IL@ZIF-8 catalyst reached above 250°C, indicating good thermal stability. The ionic liquid began to decompose at 250°C, and the main reason for the weight loss was also due to the loss of ionic liquid.

[0025] 4. N2 adsorption-desorption curve and pore size distribution

[0026] The catalyst 1% F-IL-CP@ZIF-8 was tested for nitrogen adsorption and desorption at 77 K. The results are shown in Figure 4. From the figure, it can be seen that the adsorption isotherm is a typical type I isotherm, indicating microporous adsorption with a pore size distribution between 0.8 and 1.3 nm. The specific surface area of ​​the catalyst was tested to be approximately 1332 m 2 g -1 According to the literature, the specific surface area of ​​traditional ZIF-8 is about 1800 m2 g -1 The decrease in specific surface area may be due to the loading of ionic liquid. For non-porous ionic liquid, the composite material after ionic liquid loading on ZIF-8 still maintains the large specific surface area characteristic of ZIF-8, which is conducive to gas adsorption and catalytic reaction.

[0027] 5. CO2 adsorption test and isosteric adsorption heat

[0028] The catalyst 1% F-IL-CP@ZIF-8 was tested for CO2 adsorption and desorption at 298K and 273K, respectively. The results are shown in Figure 5. It can be seen from the figure that the maximum adsorption of CO2 at 298K and 273K is 14.9cm 3 g -1 and 28.6cm 3 g -1 , showing that the catalyst has good CO2 adsorption performance. At the same time, the affinity of the catalyst for CO2 was explored. Through the Virial equation calculation, the isosteric adsorption heat Qst value of CO2 of the catalyst 1% F-IL-CP@ZIF-8 was calculated to be 17.45 kJ / mol, indicating that it has strong physical adsorption capacity at low CO2 coverage.

[0029] 6. EDX spectrum analysis

[0030] The EDX spectrum analysis of the catalyst 1%F-IL-CP@ZIF-8 was carried out. Figure 6 The data tested by the energy spectrometer are shown in Table 1, from which we can see the content of each element, including C, N, O, Zn, Br, F and other elements.

[0031] Table 1 Element contents of 1%F-IL-CP@ZIF-8 catalyst

[0032]

[0033] 3. Study on the catalytic cycloaddition reaction of CO2 and epoxides

[0034] The specific experimental process of the cycloaddition reaction of CO2 and epoxide is as follows: add the required amount of catalyst to the Schlenk tube, then evacuate the tube three times to discharge the gas in the tube, slowly add epichlorohydrin to the Schlenk tube (0.925g, 10mmol), connect a balloon filled with CO2 (0.1 MPa) to the tube mouth, and put it in an oil bath and heat it to the preheating temperature. After the reaction is completed, remove the Schlenk tube from the oil bath, cool it to room temperature, discharge the remaining CO2, take out the product, and perform quantitative analysis by NMR peak area to calculate the cyclocarbonate conversion rate.

[0035] 1. Catalytic performance of ionic liquid catalysts with different loading amounts

[0036] To explore the catalytic performance of the catalyst, CO2 and epichlorohydrin (ECH) were used as model compounds. The cycloaddition reaction was carried out under the conditions of epichlorohydrin (0.925 g, 10 mmol), CO2 pressure 0.1 MPa, 80 °C, solvent-free and co-catalyst-free to screen out the catalyst with the best performance. The catalytic activity was as follows: Figure 7 As shown. Experimental data show that when ZIF-8 is used directly as a catalyst, its catalytic activity is only 27%, which is relatively low. When using ionic liquid catalysts with different loading amounts, it is found that when the loading amount is 1%. Its catalytic performance can reach 97.4%. With the increase of the loading amount, its activity remains basically stable. When the loading amount is 10%, its activity decreases significantly. The reason may be that the excessive loading of ionic liquid causes the pores and active sites of ZIF-8 to be blocked. In summary, we selected the catalyst with a loading amount of 1% as the optimal catalyst.

[0037] 2. Influence of reaction temperature

[0038] The CO2 cycloaddition reaction was carried out at different reaction temperatures using the optimal catalyst 1%F-IL-CP@ZIF-8. Figure 8 As shown in the figure, the catalytic activity is constantly increasing with the increase of temperature. When the temperature reaches 80°C, the reaction activity reaches the maximum value. When the temperature continues to rise, it is found that the activity has basically not changed. Therefore, the reaction temperature of 80°C is the optimal reaction temperature.

[0039] 3. Impact of reaction time

[0040] The CO2 cycloaddition reaction was carried out at different reaction times using the optimal catalyst 1%F-IL-CP@ZIF-8. Fig. 9 As shown in the figure. According to the data in the figure, the catalytic activity is constantly increasing with the increase of time. When the reaction time reaches 48h, the reaction activity reaches the maximum value. When the reaction time continues to increase, it is found that the activity has basically not changed. Therefore, the reaction time of 48 h is the optimal reaction time.

[0041] 4. Study on the applicability of different epoxide substrates

[0042] Through the screening of catalysts and the optimization of various reaction conditions, 1%F-IL-CP@ZIF-8 was selected as the optimal catalyst. The substrate adaptability of the 1%F-IL-CP@ZIF-8 catalyst was explored by the experiment of cycloaddition reaction of 5 different epoxides such as oxirane, butylene oxide, phenyl glycidyl ether, butyl glycidyl ether, and styrene oxide with CO2 to generate cyclic carbonates. The results are shown in Table 2 below. The experimental results show that the 1%F-IL-CP@ZIF-8 catalyst can achieve excellent activity for different substrate yields, but for epoxides with large steric hindrance, due to the enhanced conjugation effect, the yield will be lower.

[0043] Table 2 Effect of 1% F-IL-CP@ZIF-8 catalyst on the cycloaddition reaction of CO2 with different epoxides

[0044]

[0045] 5. Study on catalyst stability

[0046] The optimal catalyst 1%F-IL-CP@ZIF-8 was tested cyclically at a reaction temperature of 80°C, a reaction time of 48h, and a CO2 pressure of 0.1Mpa. Fig.10 As shown. The catalyst after the reaction was recovered by centrifugation, repeatedly rinsed with methanol, filtered and dried for continued use. After the catalyst was recycled for 5 times, its activity did not decrease significantly, indicating that the catalyst had good stability. When the activity was found to be significantly reduced in the 6th cycle, it may be caused by the blockage and collapse of the pores of the catalyst after repeated use.

[0047] The catalytic mechanism of catalyst 1%F-IL-CP@ZIF-8 is:

[0048]

[0049] First, the Lewis acid sites of the catalyst electrophilically activate the epoxide ring, resulting in the ring opening of the epoxide. Next, the Br anion nucleophilically attacks the CO2 oxygen atom and combines with the carbon of the epoxide to form an intermediate metal species. Finally, the oxygen anion and the carbon atom of CO2 undergo intramolecular cyclization to form a cyclic carbonate, while the catalyst is regenerated and recycled to the next reaction.

[0050] In summary, the present invention prepares IL@MOF composite materials by loading ionic liquid onto ZIF-8 through a solid phase synthesis method, and applies it to the cycloaddition reaction of CO2 and epoxide. By comparing the catalytic performance of ionic liquids with different loading amounts, it is found that the activity effect is optimal when the loading amount is 1.0%, and an excellent conversion rate of cyclic carbonate is shown under solvent-free and co-catalyst conditions. At the same time, the synthesized composite material has a large specific surface area, good recyclability and good stability, and is a composite catalyst of ionic liquid and MOF with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The morphology structure diagram of the 1%F-IL-CP@ZIF-8 catalyst prepared by the present invention, wherein (a) is a transmission electron microscope image of ZIF-8, (b) is a transmission electron microscope image of 1%F-IL-CP@ZIF-8, (c) is a scanning electron microscope image of 1%F-IL-CP@ZIF-8 at a magnification of 10 μm, and (d) is a scanning electron microscope image of 1%F-IL-CP@ZIF-8 at a magnification of 5 μm;

[0052] Figure 2 X-ray powder diffraction patterns of ZIF-8 catalysts with different ionic liquid loadings prepared by the present invention;

[0053] Figure 3 This is the thermogravimetric spectrum of the 1% F-IL-CP@ZIF-8 catalyst prepared in the present invention;

[0054] Figure 4 shows the N2 adsorption-desorption curve and pore size distribution diagram of the 1% F-IL-CP@ZIF-8 catalyst prepared in the present invention at 77 K, where (a) is the N2 adsorption-desorption curve and (b) is the pore size distribution diagram;

[0055] Figure 5 shows the CO2 adsorption-desorption curve and isosteric adsorption heat curve of the 1% F-IL-CP@ZIF-8 catalyst prepared in the present invention at 298 K and 273 K, where (a) is the CO2 adsorption-desorption curve, and (b) is the CO2 isosteric adsorption heat curve;

[0056] Figure 6 This is the EDX spectrum of the 1% F-IL-CP@ZIF-8 catalyst prepared by the present invention;

[0057] Figure 7 Comparative diagram of catalytic performance of ionic liquid catalysts with different loading amounts prepared by the present invention;

[0058] Figure 8 The relationship curve of the catalytic performance of the 1% F-IL-CP@ZIF-8 catalyst prepared by the present invention as a function of temperature;

[0059] Fig. 9 This is a curve showing the relationship between the catalytic performance of the 1% F-IL-CP@ZIF-8 catalyst prepared by the present invention and the change over time;

[0060] Fig.10 This is a graph showing the cycle test results of the 1% F-IL-CP@ZIF-8 catalyst prepared in the present invention. DETAILED DESCRIPTION

[0061] The synthesis method of the 1% F-IL-CP@ZIF-8 catalyst of the present invention is as follows:

[0062] Synthesis of tetrafluoro-1,4-di(bromomethyl)benzene: Place 1.2g (5.71mmol) of tetrafluoro-1,4-di(hydroxymethyl)benzene in a 100ml round-bottom flask, add 50ml of dichloromethane after distillation, and cool in an ice bath. Slowly add 3.74g (14.26mmol) of triphenylphosphine and 4.73g (14.26mmol) of carbon tetrabromide, remove from the ice bath and heat to room temperature, stir slowly, observe the color change from orange to black to light yellow, then stir at high speed, stir at room temperature for 24h, and monitor the reaction progress with a TLC plate during the reaction. After stirring stops, the crude product is removed from the solvent by a rotary evaporator, and then the crude product is purified by column chromatography, the developing solvent is pure petroleum ether, and the product is repeatedly rinsed with dichloromethane, filtered, and vacuum dried overnight to obtain white crystals. (Yield: 1.4g, 76%)

[0063] Synthesis of catalyst F-IL-CP: 1.34 g (4 mmol) of tetrafluoro-1,4-di(bromomethyl)benzene and 2.24 g (8 mmol) of tricyclohexylphosphine were added to a 100 ml round-bottom flask, followed by 60 ml of distilled dichloromethane. The mixture was stirred at room temperature for 24 h, and the reaction progress was monitored by TLC plates during the reaction. After stirring was stopped, the crude product was subjected to a rotary evaporator to remove the solvent, the residue was collected and washed with ether three times to remove unreacted substances, filtered, and vacuum dried at 50 ° C overnight to obtain a white solid. (Yield: 2.3 g, 65%)

[0064] Synthesis of catalyst 1% F-IL-CP@ZIF-8: Zinc oxide (12.5 mmol, 1 g), 2-methylimidazole (26.7 mmol, 2.2 g) and ionic liquid F-IL-CP (27.5 mg) were put into a mortar by solid phase synthesis method, and ground thoroughly with a mortar pestle to make them evenly mixed. After that, the ground mixture was poured into a reactor equipped with a polytetrafluoroethylene liner, placed in an oven, and the temperature was adjusted to 160 °C for 24 h. After the reaction, the reactor was taken out, and after the temperature was cooled to room temperature, the solid in the liner was taken out, washed with methanol 3 times, and finally placed in an oven to dry overnight to obtain 2.26 g of white solid. By adjusting the mass of the added ionic liquid, MOFs with different loading amounts can be formed.

[0065] Structural characterization and performance evaluation Figure 1-10 .

Claims

1. A method for preparing a bifunctional heterogeneous catalyst, characterized in that: The following steps are involved: 1) Synthesis of tetrafluoro-1,4-di(bromomethyl)benzene Using dichloromethane as solvent and triphenylphosphine as initiator, tetrafluoro-1,4-di(hydroxymethyl)benzene and carbon tetrabromide were stirred and reacted at room temperature for 20-24 hours, washed, filtered, and vacuum dried to obtain tetrafluoro-1,4-di(bromomethyl)benzene; 2) Synthesis of F-IL-CP ionic liquid Tetrafluoro-1,4-di(bromomethyl)benzene and tricyclohexylphosphine were dissolved in dichloromethane, stirred at room temperature for 20-24 hours, washed, filtered, and vacuum dried to obtain F-IL-CP ionic liquid; 3) Synthesis of catalyst 1%F-IL-CP@ZIF-8 Zinc oxide, 2-methylimidazole and F-IL-CP ionic liquid were ground and mixed, reacted at 150-170°C for 20-24h, washed and dried to obtain the catalyst 1% F-IL-CP@ZIF-8.

2. A method for preparing a bifunctional heterogeneous catalyst as claimed in claim 1, characterized in that: In step 1), the molar ratio of tetrafluoro-1,4-di(hydroxymethyl)benzene to carbon tetrabromide is 1:(2-5), and the molar ratio of triphenylphosphine to carbon tetrabromide is 0.8:1-1:1.

2.

3. A method for preparing a bifunctional heterogeneous catalyst as claimed in claim 1, characterized in that: In step 2), the molar ratio of tetrafluoro-1,4-di(bromomethyl)benzene to tricyclohexylphosphine is 1:1.5 to 1:2.

5.

4. A method for preparing a bifunctional heterogeneous catalyst as claimed in claim 1, characterized in that: In step 3), the molar ratio of zinc oxide to F-IL-CP ionic liquid is 40-60:1, and the molar ratio of zinc oxide to 2-methylimidazole is 1:1.5-1:2.

5.

5. Use of the bifunctional heterogeneous catalyst prepared by the method as claimed in claim 1 in catalyzing the cycloaddition conversion of CO2 and epoxide.

6. The use of the bifunctional heterogeneous catalyst as claimed in claim 5 in catalyzing the cycloaddition conversion of CO2 and epoxide, characterized in that: Using 1% F-IL-CP@ZIF-8 as catalyst, CO2 and epoxide underwent cycloaddition reaction at 80 °C for 48 h.

Citation Information

Patent Citations

  • ZIF-8 encapsulated amino ionic liquid type carbon dioxide adsorbing-catalyzing agent

    CN105149002A

  • Method for catalyzed synthesis of cyclic carbonate through functional metal organic frame material

    CN105481821A